Mamluks, Property Rights, and Economic Development: Lessons from Medieval Egypt. (September 2019) - Blaydes, Lisa
Secure property rights are considered a common institutional feature of rapidly growing economies. Although different property rights regimes have prevailed around the world over time, relatively little scholarship has empirically characterized the historical property rights of societies outside Western Europe. Using data from Egypt's Mamluk Sultanate (1250–1517 CE), this article provides a detailed characterization of land tenure patterns and identifies changes to real property holdings associated with an institutional bargain between Egypt's slave soldiers—the mamluks—and the sultan. Although agricultural land was a collective resource of the state, individual mamluks—state actors themselves—established religious endowments as a privatizing work-around to the impermissibility of transferring mamluk status to their sons. The article's characterization of landholding patterns in medieval Egypt provides an empirical illustration of how Middle Eastern institutions differed from those in other world regions as well as an understanding for how and why regimes come under political stress as a result of their property rights institutions.